Answer:[m, m+d, m+2d, - - - - -, n]
Step-by-step explanation:
We know the formula for arithmetic progression is a_(n) = a_(1) + (n-1)d
Where a_(n) is the nth term of the sequence
a_(1) is the first term of the sequence
n is the number of the term like if we are talking about 7th term so the n is 7.
d is the difference between two successive terms.
For this problem we know our first term that is m, our last term that is n and our difference that is d.
For second term we will use the formula
a_(2) = m + (2-1)d
a_(2) = m + (1)d
a_(2) = m + d
Similarly,
a_(3) = m + (3-1)d
a_(3) = m + (2)d
a_(3) = m + 2d
Answer:
Step-by-step explanation:
The graph that represents the function
f(x) = (x + 4)(x + 1)(x - 3)
crosses the x-axis three times: at x = -4, x = -1, and x = 3
because we apply the zero product rule and found the roots -4, -1, and 3
x+ 4= 0 → x = -4
x+1 = 0 → x = -1
x-3 = 0 → x = 3
Answer:
C -(-6.53)+4.11-(-7.92)−(−6.53 )+4.11−(−7.92)minus, left parenthesis, minus, 6, point, ...
Answer: Choice B and Choise C.Step-by-step explanation: Equivalent expressions are those expressions that have the same value but they look different.
Answer: Three dimensional
Step-by-step explanation:
A rectangular prism is a three-dimensional shape.
[] A one-dimensional shape is a line
[] A two-dimensional shape is a rectangle, circle, etc
[] This means that a rectangular prism is a three-dimensional shape